Correction: Influence of Y-substitution on phase composition and proton uptake of self-generated Ba(Ce, Fe)O3−δ–Ba(Fe, Ce)O3−δ composites. Issue 32 (2nd August 2022) - Berger, Christian; Bucher, Edith; Merkle, Rotraut; Nader, Christina; Lammer, Judith; Grogger, Werner; Maier, Joachim; Sitte, Werner
Abstract : Correction for 'Influence of Y-substitution on phase composition and proton uptake of self-generated Ba(Ce, Fe)O3− δ –Ba(Fe, Ce)O3− δ composites' by Christian Berger et al., J. Mater. Chem. A, 2022, 10, 2474–2482, ; https://doi.org/10.1039/D1TA07208K .